Evapotranspiration in High-Yielding Maize and under Increased Vapor Pressure Deficit in the US Midwest - Bruno Basso; Joe T. Ritchie (Agricultural & Environmental Letters, 2018)
This paper describes the results of an analysis demonstrating that high yields in maize can be obtained without additional water under current and projected vapor pressure deficits. The objective of the study was to quantify evapotranspiration (ET) in high-yielding maize under current and projected vapor pressure deficits using the energy balance contrasted with the transpiration efficiency (TE) approach. This study indicates a lack of accuracy and bias in the TE approach when future crop water requirements were estimated. High maize yields are achievable using on average 700 mm of water as demonstrated by the current record maize grain yield of 34 Mg ha, which is ∼23 Mg ha higher than the US average. These yields are achievable with approximately the same ET even under projected changes in vapor pressure deficit, through improved genetics and optimum agronomic management.